2023
DOI: 10.1080/07853890.2022.2163282
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of air pollution exposure on the risk of preterm birth in Xi’an, China

Abstract: Introduction Long-term exposure to air pollution is known to be harmful to preterm birth (PTB), but little is known about the short-term effects. This study aims to quantify the short-term effect of particulate matter with aerodynamic diameter ≤ 2.5 μm (PM 2.5 ), ≤10 μm (PM 10 ) and nitrogen dioxide (NO 2 ) on PTB. Materials and methods A total of 18,826 singleton PTBs were collected during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…He et al showed a correlation between SO 2 and preterm birth in mid- and late-pregnancy, which is similar to our results [ 35 ]. A study of short-term exposure to air pollutants in preterm birth in Xi'an, China, demonstrated a correlation between SO 2 and preterm birth [ 36 ]. Some studies have found that exposure to high levels of CO in early pregnancy and throughout pregnancy leads to an increased risk of very preterm birth [ 37 ], this is similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…He et al showed a correlation between SO 2 and preterm birth in mid- and late-pregnancy, which is similar to our results [ 35 ]. A study of short-term exposure to air pollutants in preterm birth in Xi'an, China, demonstrated a correlation between SO 2 and preterm birth [ 36 ]. Some studies have found that exposure to high levels of CO in early pregnancy and throughout pregnancy leads to an increased risk of very preterm birth [ 37 ], this is similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only a few studies have observed associations between neighborhood deprivation and the prevalence of birth defects overall, but one showed an association between increased neighborhood deprivation and higher prevalence of gastroschisis ( 50 , 78 ). Some studies report positive associations with air pollution and preterm birth, especially with NO 2 ( 79 81 ). Further research has identified that neighborhood deprivation is associated with increased preterm birth risk and one study demonstrated that neighborhood deprivation and urbanicity are associated with a higher risk, implying that there may be risks associated with the interaction between neighborhood deprivation and traffic-related air pollution ( 38 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of assessment of exposure in different trimesters of pregnancy, and the mechanisms by which air pollution affects the growth and development of the fetus [75]. Exposure to air pollution during late pregnancy can cause inflammation and, by causing hypoperfusion of the placenta, lead to preterm birth (PTB) [76].…”
Section: Causes Of Oxidative Stress In Pregnancymentioning
confidence: 99%